Assessing Effect of the Reagglomeration and Migration of Chemical Curatives on the Mechanical Properties of Natural Rubber Vulcanizate. Issue 1 (9th February 2012) - Saeed, Farhan; Ansarifar, Ali; Ellis, Robert J.; Haile‐Meskel, Yared
Abstract Natural rubber was mixed with a high loading of a sulfur‐bearing silanized silica nanofiller and cured by adding a sulfenamide accelerator and zinc oxide. The rubber was cured at 85° and 140°C, which were below and above the melting point of the accelerator, respectively, and stored at ambient temperature for up to 60 days to allow full blooming to appear. The mechanical properties of the rubber vulcanizate were measured and found to be affected by the blooming of the accelerator on the rubber surface, which also damaged the internal structure of the rubber. Below the melting point of the accelerator there was little or no reagglomeration and some migration of the accelerator, whereas above the melting point there were reagglomeration and extensive migration of the accelerator to the rubber surface. The latter was more damaging to the rubber properties than the former. © 2012 Wiley Periodicals, Inc. Adv Polym Techn 32: E153–E165, 2013; View this article online at wileyonlinelibrary.com. DOI 10.1002/adv.21259